2023
DOI: 10.3390/v15061301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermediate Plus Vaccine and vvIBDV on Bursa Secretory Cells and Their Glycoprotein Production

Abstract: There are two types of secretory cells in the chicken bursa of Fabricius (BF): (a) interfollicular epithelial cells (IFE), and (b) bursal secretory dendritic cells (BSDC) in the medulla of bursal follicles. Both cells produce secretory granules, and the cells are highly susceptible to IBDV vaccination and infection. Before and during embryonic follicular bud formation, an electron-dense, scarlet-acid fuchsin positive substance emerges in the bursal lumen, the role of which is unknown. In IFE cells, IBDV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The tumor-associated antigen MUC1+/+ is expressed by dendritic cells in synovial fluid of patients with arthritis, but not by healthy thymic or tonsillar dendritic cells ( Cloosen et al, 2004 ). Mouse dendritic cells produce mucin-like glycoprotein ( Williams et al, 2010 ) and we have recently reported glycoprotein secretion by the chicken BSDC ( Felföldi et al, 2021 ; Oláh et al, 2022 , 2023 ), which suggests some general features for the warm-blooded vertebrates (birds and mammals).…”
Section: Function Of Bsdcmentioning
confidence: 91%
See 1 more Smart Citation
“…The tumor-associated antigen MUC1+/+ is expressed by dendritic cells in synovial fluid of patients with arthritis, but not by healthy thymic or tonsillar dendritic cells ( Cloosen et al, 2004 ). Mouse dendritic cells produce mucin-like glycoprotein ( Williams et al, 2010 ) and we have recently reported glycoprotein secretion by the chicken BSDC ( Felföldi et al, 2021 ; Oláh et al, 2022 , 2023 ), which suggests some general features for the warm-blooded vertebrates (birds and mammals).…”
Section: Function Of Bsdcmentioning
confidence: 91%
“…During the last 45 yr, we have published numerous papers about the structure ( Olah and Glick, 1987 ), characterization ( Olah et al, 1992 ; Olah and Glick, 1992 ; Pharr et al, 1995 ; Oláh and Nagy, 2013 ; Nagy et al, 2016 ), changes in the experimental condition ( Olah and Glick, 1978b , 1986 ; Olah et al, 1979 ), glycoprotein production ( Felföldi et al, 2021 ; Oláh et al, 2022 ) and effect of IBDV infection ( Felföldi et al, 2022 ; Oláh et al, 2023 ) of the BSDC.…”
Section: Introductionmentioning
confidence: 99%